Comparative Critique of Jahanbakhsh’s Personality Based on the Borzou and Rostam’s Book - Mohammadreza Rashed Mohassel, Seyed Jamal Vaziri Mahboob, Aboalghasem Ghavam (Opción, 2019)
This paper is a qualitative research which aims to compare the labors of both literary works through a descriptive-analytic method. The author then does a comparative analysis of the structure and discourse of Jahanbakhsh labors in both works. As a conclusion, comparing seven labors in both works reveals that the author of New Bourzu-Nameh has had a more creative approach in the description of seven labors by paying close attention to the plot, story sequences, details, personification and characters’ behaviors.